CBIO-02. COMPREHENSIVE ANALYSIS OF MECHANISMS AND MOLECULAR TARGETS FOR BREAST CANCER LEPTOMENINGEAL METASTASIS. (9th November 2020) - Kijima, Noriyuki; Achiha, Takamune; Nakagawa, Tomoyoshi; Hirayama, Ryuichi; Kinoshita, Manabu; Kagawa, Naoki; Kishima, Haruhiko
Abstract: Leptomeningeal metastasis from solid cancer is a devastating state for cancer patients. Leptomeningeal metastasis is diagnosed either by cerebrospinal fluid cytology and/or magnetic resonance imaging (MRI). However, it remains unclear as to whether tumor cells attached to leptomeninges are the same from floating tumor cells in cerebrospinal fluid (CSF). In this study, we aim to analyze the differences between tumor cells attached to leptomeninges and floating cells in CSF by xenograft models. We used breast cancer cell line, MDA-MB-231, labelled with green fluorescent protein (GFP) and luciferase. We injected those cells into right lateral ventricle of NOD/Shi-scid IL2Rγ KO mice. When the mice got any signs of tumor, we dissected spinal cord and got CSF from mice. We sorted tumor cells by flow cytometry and extracted RNA from the sorted tumor cells from spinal cord and CSF, respectively. We analyzed transcriptome differences between tumor cells from spinal cord and CSF by RNA sequencing. We found that extracellular matrix related proteins were highly upregulated while cell growth related proteins were downregulated in tumor cells from spinal cord compared with those from CSF. These results suggest that tumor cells attached to leptomeninges have different transcriptome profiles from floating tumor cells in CSF and extracellular matrix related proteins could be therapeutic targets for breast cancer leptomeningeal metastasis.